Intercropping as a Farmer Adaptation Strategy During Drought: A Case Study of Karangwuni and Semugih Sub-districts, Gunungkidul - Devrina Nur Azizah; Eva Banowati; Juhadi Juhadi; Rahma Hayati; Erni Suharini (Universitas Lambung Mangkurat, 2026)
Gunungkidul Located in a Mediterranean soil complex with a high lime content and low organic matter content, this area is prone to lithological drought. The impacts of the disaster begin to be felt during the dry season. long-term impacts on agricultural productivity. One of the adaptation strategies implemented by farmers is intercropping, which is able to face socio-economic dynamics during times of drought . This study aims to analyze farmers' adaptation strategies from both the physical (environmental) or non-physical including social, economic and institutional . This research uses Quantitative methods with descriptive statistical analysis based on the Likert Scale and Google Earth Engine imagery for calculating the Vegetation Health Index, processed through ArcGIS. Data were collected through surveys, questionnaire interviews, focus group discussions , and documentation with sampling using non probability sampling quota sampling technique based on the Dixon and B. Leach formula , involving 84 farmers and 5 village institutions in Suruh, Karangwuni Subdistrict and Kemesu, Semugih Subdistrict. These findings indicate The strategies implemented by farmers vary between Dukuh Suruh and Dukuh Kemesu, namely: 1) physical adaptation of environmental aspects 87% of land and water management, 2) social 79-81% with mutual cooperation in routine discussions with farmer groups, 3) economic 75-76% diversifying income and storing harvests in the form of food reserves before being sold, and 4) institutional 85-95% of village government programs for water distribution assistance and training during drought.